FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA GURU - Hasanah Hasanah Hasanah (Manajer Pendididikan, 2015)
This research aim to describe of internal and eksternal factors which influence satisfaction of teacher in activity. Any kind of becoming supplementary factor and resistor influencing teacher performance. Research instrument to be used by interview in study of deskiptif qualitative. Expected by result of this research will give optimal usefulness either through academic or theoretical and also practically. Thereby result of this research is expected can give contribution to science world and technology. From result of research, can be concluded that satisfaction of activity learn in yunior high school Town of Lubuklinggau can be influenced byservice in school, prosperity of teacher, and positive factor able to improve result learn student.Keyword: factors, taecher’s satisfaction